Temperature Rise Increases the Bioavailability of Marine Synechococcus-Derived Dissolved Organic Matter - Zhang, Jiajie; Liu, Jihua; Liu, Daixi; Chen, Xiao; Shi, Quan; He, Chen; Li, Gang (Frontiers in Microbiology, 2022)
Synechococcus is one group of main primary producers and plays a key role in oceanic carbon fixation and transformation. To explore how the temperature rise affects the bioavailability of Synechococcus-derived dissolved organic matter (SOM) and whether this effect would be altered by the involvement of heterotrophic bacteria, we compared the optical and molecular properties of the SOM of axenic Synechococcus sp. PCC7002 culture (Syn) to that with associated heterotrophic bacteria (SynB) under 15, 18, and 21°C growth temperatures at exponential and decay growth phases. Our results showed that the temperature rise increased the bioavailability of the SOM of both Syn and SynB cultures by lowering the proportion of the hydrogen-poor and double-bond structure-rich humus-like components and highly unsaturated substances, as indicated by the increase of spectral slope ratio (SR) and biological index (BIX) and decrease of humification index (HIX). Moreover, the involvement of heterotrophic bacteria modified the Synechococcus-derived SOM, together with its intracellular dissolved organic matter (DOM) excludes, lowering the SOM bioavailability. Our results indicated that the warming in climate change scenario may enhance the bioavailability of the Synechococcus-derived SOM although it may be tempered by the involvement of heterotrophic bacteria, providing an insight for preservation of the organic carbon pool in global oceans.